Evaluation of a free amino acid–based formula in infants with presumptive food protein–induced proctocolitis. (20th September 2014) - Borschel, Marlene W; Antonson, Dean L; Murray, Nancy D; Oliva-Hemker, Maria; Mattis, Lynn E; Baggs, Geraldine E
Objective: Food protein–induced proctocolitis usually occurs early in life and is characterized by blood-streaked stools and pain during defecation in an otherwise healthy infant. While many infants with food protein–induced proctocolitis respond well to a casein hydrolysate formula, some require an amino acid–based formula. The objective of the study was to measure the change in physician-rated symptom score from enrollment to study completion in infants with presumptive food protein–induced proctocolitis fed with a specific amino acid-based formula. Methods: In this study, infants ≤6 months of age diagnosed with presumptive food protein–induced proctocolitis received an amino acid-based formula for 42 days. Intake, stool patterns, weight, stool occult blood, and questionnaires assessing infant feeding and stool patterns and parental formula satisfaction were collected. Results: The full analysis set included 43 infants. The mean age at enrollment was 59 ± 5 days. A significant improvement was observed from enrollment to exit in physician-rated symptom score (9.1 ± 0.5 to 4.8 ± 0.5, p < 0.0001), the number of infants with occult blood in stool, and weight-for-age Z-scores during the study. Parental satisfaction with the formula was high. Conclusion: The results confirm that the amino acid-based formula studied is efficacious for managing symptoms of presumptive food protein–induced proctocolitis.